Effect of Short-Term Tacrolimus Exposure on Rat Liver: An Insight into Serum Antioxidant Status, Liver Lipid Peroxidation, and Inflammation. (24th February 2021) - Fatima, N.; Sheikh, N.; Satoskar, A. R.; Akhtar, T.; Tayyeb, A.; Ashfaq, I.; Ryan, N.; Ambreen, S.; Jha, B. K.; Oghumu, S.
Abstract : Tacrolimus (TAC) is an immunosuppressive drug, optimally used for liver, kidney, and heart transplant to avoid immune rejection. In retrospect, a multitude of studies have reported effects of TAC, such as nephrotoxicity, diabetes, and other complications. However, limited information is available regarding short-term exposure of TAC on the liver. Therefore, the present study was designed to unravel the effects of short-term exposure of TAC on a rat model. The animal model was established by TAC administration for 6, 12, 24, and 48 h time points. Liver histopathological changes were observed with PAS-D, reticulin stain, and immunostaining of PCNA and CK-7 coupled with glycogen quantification in a liver homogenate. TUNEL assay was performed to evaluate the DNA damage in the liver. Concentration of GSH and activities of SOD and CAT in the serum were measured to assess the antioxidant status, whereas liver tissue MDA level was measured as a biomarker of oxidative stress. Hepatic gene expression analysis of IL-10, IL-13, SOCS-2, and SOCS-3 was performed by RT-PCR. Results revealed marked changes in liver architecture of all TAC-treated groups, as evidenced by sinusoid dilation, hepatocyte derangement, glycogen deposition, and collapsed reticulin fibers. Significant increase in PCNA and CK-7 immunostaining along with the presence of TUNEL-positive cells was revealed in treatment groups as compared to the control group. Serum antioxidant enzyme status was markedly decreased, whereas the liver MDA level was increased in TAC treatment groups indicating oxidative stress induction. The gene expression profile of cytokines was significantly upregulated in treatment groups highlighting an inflammatory response. In conclusion, results of the current study propose that even a short-term TAC exposure can induce change in antioxidant status and lipid peroxidation. Therefore, these factors should be considered to avoid and minimize immunosuppression-related issues in a prolonged course of treatment.